Research on Public Open Space of Rural Areas in Severe Cold Regions Based on Survey of Residents on the Behavioral Activity. (2016) - Leng, Hong; Li, Tong
Abstract: This paper took towns and villages in the cold northeast regions as the survey objects, making a detailed research on residents' behavioral activity in public open space on the basis of a large number of household interviews and questionnaires, and to analysis the laws of use, using effect and influencing factors. Then common problems about various types of public open space of rural areas in cold regions were summarized, and some recommendations on the public open space planning would be given.